Cardiopulmonary Rehabilitation in Elderly Patients with Heart Failure: A Prospective Cohort Study. (1st April 2022) - Zhou, Haitao; Dong, Aishu; Xu, Xiaoqing; Zhu, Jianing; Shi, Bowen
Abstract : Objective . To determine the impact of cardiopulmonary rehabilitation administered through WeChat on exercising resilience and life quality in aged people with heart failure (HF). Methods . We conducted prospective cohort study that included 80 heart failure patients who were admitted to the Second Affiliated Hospital of Wenzhou Medical University from June 2018 to September 2020, 80 patients with heart failure. Patients were grouped according to their use of WeChat for rehabilitation. WeChat cohort provides remote supervision of rehabilitation and nursing guidance through WeChat. Specifically, the findings below were predetermined and compared across treatment groups utilizing analysis of variance corrected for baseline levels of the end measure and location: changes in the length of cardiopulmonary exercise tests, peak VO2, the proportion of predicted maximum VO2, and variation in the distance covered during the 6-minute walk distance (6MWD) assessment. Comparison of negative emotions between two groups, a Self-rating Depression Scale (SDS) and Self-rating Anxiety Scale (SAS), and Survey Short Form-36 (SF36) at baseline and at month 2. Results . In contrast with the control cohort, the WeChat cohort did not show any significant differences in general data (P > 0.05). After the rehabilitation, the WeChat group has a notably higher level in 6MWD than in the control group. Prior to the rehabilitation, there were no statistical gaps between the two cohorts in terms of SAS and SDS scores (P > 0.05). Even though the two cohorts saw a decline in SAS and SDS scores following nursing, the observation cohort indicated a much relatively low level in contrast with the control cohort (P < 0.05). The comparison of the SF-36 scores between the two cohorts revealed no significant differences (P > 0.05). Following nursing, the scores of the two cohorts declined significantly, with the control cohort scoring far lower than the other (P < 0.05). Conclusions . In summary, cardiopulmonary rehabilitation via WeChat is very beneficial for HF patients who are at a stable phase of the disease. It may substantially improve patients' exercise stamina, reduce adverse emotions, boost patients' quality of life, and have significant clinical relevance.